Common grammatical errors in the writing of high school students in Jordan - Tarawneh, Sudgeh Awad Falaah (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to identify the common grammatical errors in the written expression of high school students in Jordan, and to identify the level that enables the students to employ grammatical skills in their writing. The sample of the study consisted of (42) high school students who were assigned to write an expressive topic in about (150) words in two topics that were identified by the researcher, and after the students ’papers were corrected and the grammatical errors were classified in their writings, the results of the research showed that the number of types of errors The grammatical expression in the written expression of high school students totaled (58) grammatical errors, the percentage of those errors ranged between (5.17% - 18.97%) and the type of error (the syntax of the plural of the peaceful masculine) came in the first place, as the number of this error reached (11) errors. With percentages amounting to (18.97), and the error came in (the sentence of Anna and her sisters) with a frequency of (10) occurrences with a percentage of (17.24%), followed by the error in (Kana's sentence and its sisters) with a frequency of (9) iterations and a percentage of (15.52) The error in (the parsing of al-Muthanna) came in fourth place with (8) iterations with a percentage of (13.79%), followed by the error in (number and count) with a frequency of (7) errors with a percentage of (12.07%), followed by a mistake (Assert the present tense verb ineffective) enumerates (6) iterations with a percentage of (10.34%), followed by a mistake (the parsing of the five verbs) after occurrences of (4) occurrences and a percentage of (6.90%), and the error in (parsing the five names) came in the last place with a number of (3) occurrences and a percentage of (5.17%). The results also showed that the standard percentages of the types of grammatical errors common in written expression among high school students ranged between (5.17% - 18.97%), all of which were less than (40%), which indicates that high school students have a good level of employing grammar skills. needed for written expression.The researcher made a number of recommendations, the most important of which are: teachers' training for students from the first basic grades on expressive writing situations, so that they get used to correctly formulating the sentence. and accustom students to reading and reading so that the circle of their culture expands and they have a linguistic wealth that helps them to write expressively.
Keywords: grammatical errors; written expression; high school students